Community-based drug demand reduction report on five demonstration projects. - United Nations Economic and Social Commission for Asia and the Pacific ([Bangkok] Economic and Social Commission for Asia and the Pacific, United Nations, New York, 1995)
Report projects on countries of South and Southeast Asia
"ST/ESCAP/1552"--Title page verso
Keywords: Drug abuse -- Asia -- Prevention -- Citizen participation